Analysis of ballistic capture in Sun–planet models. Issue 6 (15th September 2015) - Luo, Z.-F.; Topputo, F.
Highlights To assess the role played by the dynamical model and planetary eccentricity in the ballistic capture about a planet. To study the effect of planet true anomaly, in a quantitative and qualitative way. To evaluate the effect of spatial distribution on ballistic capture orbits.